ANALISA EFEKTIFITAS MIND MAPPING DALAM MENUMBUHKAN KETERAMPILAN BERPIKIR KRITIS PADA ANAK SEKOLAH DASAR - Christiana Switaningsih; Sumarno; Ida dwijayanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine the effectiveness of mind mapping in cultivating critical thinking skills in elementary school children. This study used a type of qualitative descriptive research. The data collection technique used was a questionnaire targeting fifteen teachers from five elementary schools in Semarang City. The instrument used is a questionnaire with four questions related to curriculum aspects, the use of learning media, the frequency of using mind mapping, the benefits of using mind mapping, and the constraints of using mind mapping. The results of the questionnaire can generally be stated that not all teachers often use the mind mapping learning model due to several obstacles, including: time problems and understanding of the concept of mind mapping for teachers who are still lacking. Advice for teachers and students to want to learn more about the concept of understanding mind mapping. By often applying the mind mapping learning model in the classroom will greatly help students in cultivating critical thinking skills and completeness of learning outcomes in elementary school.